Micromonospora oryzae sp. nov., isolated from roots of upland rice - Chokchai Kittiwongwattana; Dusanee Thanaboripat; Chamroon Laosinwattana; Prommart Koohakan; Nonglak Parinthawong; Chitti Thawai (My University, 2015)
An actinomycete strain, designated CP2R9-1T, was isolated from root internal tissues of upland rice (Oryza sativa). Based on a polyphasic approach, strain CP2R9-1T was characterized as a member of the genus Micromonospora. meso-Diaminopimelic acid and 3-OH-diaminopimelic acid were present in the cell-wall peptidoglycan. The polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannosides, two unidentified phospholipids and four unidentified polar lipids. Predominant menaquinones were MK-9(H4), MK-9(H6) and MK-10(H4). Whole-cell sugars consisted of ribose, xylose, arabinose and glucose. Phylogenetic analysis of the nearly complete 16S rRNA gene sequence suggested that strain CP2R9-1T was closely related to Micromonospora haikouensis 232617T (99.32 % similarity), Micromonospora carbonacea DSM 43168T (99.18 %) and Micromonospora krabiensis MA-2T (99.16 %). Strain CP2R9-1T was distinct from its closest relatives based on low levels of DNA-DNA relatedness (21.3 ± 0.1-41.7 ± 0.7 %) and phenotypic differences. The results presented in this study showed that strain CP2R9-1T represents a novel species of the genus Micromonospora, for which the name Micromonospora oryzae sp. nov. is proposed. The type strain is CP2R9-1T ( = BCC 67266T = NBRC 110007T).
Keywords: Micromonospora; Diaminopimelic acid; Strain (injury); Arabinose; Diamino acid; Genomics and Phylogenetic Studies